Oxford advanced learner's dictionary - Hornby, Albert Sydney; Wehmeier, Sally; Ashby, Michael (Oxford Oxford University Press, 1989)
This revised and updated new edition of the standard dictionary for advanced learners of English contains 57000 words and phrases, increased coverage of phrasal verbs, idioms and American English, greater focus on pronunciation and stress, and appendices on irregular verbs and punctuation.
Keywords: English language -- Dictionaries. English language. English language - Dictionaries